Rationalizing the decavanadate(V) and oxidovanadium(IV) binding to G-Actin and the competition with decaniobate(V) and ATP - Giuseppe, Sciortino (2022)
The experimental data collected over the past 15 years on the interaction of decavanadate(V) (V10O286-; V10), a polyoxometalate (POM) with promising anticancer and antibacterial action, with G-actin, were rationalized by using several computational approaches (docking, density functional theory (DFT), and molecular dynamics (MD)). Moreover, a comparison with the isostructural and more stable decaniobate(V) (Nb10O286-; Nb10) was carried out. Four binding sites were identified, named α, β, γ, and δ, the site α being the catalytic nucleotide site located in the cleft of the enzyme at the interface of the subdomains II and IV. It was observed that the site α is preferred by V10, whereas Nb10 is more stable at the site β; this indicates that, differently from other proteins, G-actin could contemporaneously bind the two POMs, whose action would be synergistic. Both decavanadate and decaniobate induce conformational rearrangements in G-actin, larger for V10 than Nb10. Moreover, the binding mode of oxidovanadium(IV) ion, VIVO2+, formed upon the reduction of decavanadate(V) by the -SH groups of accessible cysteine residues, is also found in the catalytic site α with (His161, Asp154) coordination; this adduct overlaps significantly with the region where ATP is bound, accounting for the competition between V10 and its reduction product VIVO2+ with ATP, as previously observed by EPR spectroscopy. Finally, the competition with ATP was rationalized: since decavanadate prefers the nucleotide site α, Ca2+-ATP displaces V10 from this site, while the competition is less important for Nb10 because this POM shows a higher affinity for β than for site α. A relevant consequence of this paper is that other metallodrug-protein systems, in the absence or presence of eventual inhibitors and/or competition with molecules of the organism, could be studied with the same approach, suggesting important elements for an explanation of the biological data and a rational drug design.